Enhancing Interferon Regulatory Factor 7 Mediated Antiviral Responses and Decreasing Nuclear Factor Kappa B Expression Limit HIV-1 Replication in Cervical Tissues - Rollenhage, Christiane (PLoS One, 2015)
Establishment of a productive HIV-1 infection in the female reproductive tract likely depends on the balance between anti-viral and pro-inflammatory responses leading to activation and proliferation of HIV target cells. Immune modulators that boost anti-viral and depress pro-inflammatory immune responses may decrease HIV-1 infection or replication. Polyinosinic:polycytidylic [Poly (I:C)] has been reported to down-regulate HIV-1 replication in immune cell subsets and lymphoid tissues, yet the scope and mechanisms of poly (I:C) regulation of HIV-1 replication in the cervicovaginal mucosa, the main portal of viral entry in women remain unknown. Using a relevant, underexplored ex vivo cervical tissue model, we demonstrated that poly (I:C) enhanced Interferon Regulatory Factor (IRF)7 mediated antiviral responses and decreased tissue Nuclear Factor Kappa B (NFκB) RNA expression. This pattern of cellular transcription factor expression correlated with decreased HIV-1 transcription and viral release. Reducing IRF7 expression up-regulated HIV-1 and NFκB transcription, providing proof of concept for the critical involvement of IRF7 in cervical tissues. By combining poly (I:C) with a suboptimal concentration of tenofovir, the leading anti-HIV prophylactic microbicide candidate, we demonstrated an earlier and greater decrease in HIV replication in poly (I:C)/tenofovir treated tissues compared with tissues treated with tenofovir alone, indicating overall improved efficacy. Poly (I:C) decreases HIV-1 replication by stimulating IRF7 mediated antiviral responses while reducing NFκB expression. Early during the infection, poly (I:C) improved the anti-HIV-1 activity of suboptimal concentrations of tenofovir likely to be present during periods of poor adherence i.e. inconsistent or inadequate drug use. Understanding interactions between anti-viral and pro-inflammatory immune responses in the genital mucosa will provide crucial insights for the identification of targets that can be harnessed to develop preventative combination strategies to improve the efficacy of topical or systemic antiviral prophylactic agents and protect women from HIV-1 and other sexually transmitted infections.